Issues of an improving the accuracy of energy carriers production forecasting in a computer-aided system for monitoring the operation of a gas-fired cogeneration plant. (15th October 2020) - Żymełka, Piotr; Szega, Marcin
Abstract: The article presents issues related to improving the accuracy of forecasting of combined electricity and heat production in a selected gas-fired CHP plant equipped with two gas turbines with heat exchangers and a heat accumulator. To improve the accuracy of forecasting the production of energy carriers in the considered CHP plant, it has been proposed to extend the existing computer system for supervising operation with an additional calculation module. The task of this module is to correct the forecasts for electricity and heat production obtained using gas turbine model based on correction curves. In the additional computational module of the computer system, it is proposed to use empirical functions developed with the use of operational measurements of the analysed gas turbines. In the process of preparing operational measurement data for the construction of static empirical functions, the GLR (Generalized Likelihood Ratio) algorithm was used to detect the process changes and identify the periods of operation of gas turbines in a close to steady-state. The obtained results of the analyses confirm the possibility of their use in the existing computer system of operation supervision of the CHP plant. The developed empirical models are characterized by the high quality of prediction, which is confirmed by the obtained high values of determination coefficients and low error values of the model accuracy measures. The values of the coefficient of determination R^2 are within the following ranges: from 0.9754 to 0.9936 (for gas turbine GT-1) and from 0.9138 to 0.9939 (for gas turbine GT-2). The developed empirical functions can be implemented in an additional calculation module of the computer system, increasing the accuracy of planning the production of energy carriers in a gas-fired power plant. Highlights: The advanced calibration procedure for a gas turbine model is presented. The GLR algorithm was used to detect the process changes. The k-fold cross-validation was applied in the calibration procedure. The calibration procedure was performed for two gas turbines in a CHP plant. The calibration functions increase the accuracy of production planning process.